Concepções (de ensino) de gramática: na interface livro didático/professores de língua portuguesa do 5º ano - Nóbrega, Andréia Araújo da (2012)
This research aims at analyzing grammar conception present in the Portuguese language book A Escola é Nossa , used in the 5th Elementary school year of municipal schools in the town of Caicó - RN, confronting it with the grammar conception of those teachers who use such book. It is known that the Portuguese language didactic book (DB) represents an outstanding tool concerning the teaching and practice processes of language. By means of the DB, grammar can be studied in parts, as a module apart from linguistic analysis as well as from textual content. Hence, the DB framework can reflect the way the teacher conceives grammatical content. Having as starting point the hypothesis that the DB and teacher share the same conception, we do question: What is the grammar conception of the Portuguese language DB of the Elementary teaching? What is the grammar conception of the teacher who uses it? Do these conceptions demonstrate coherence in relation to PCNs´s proposals? In search of answers for such questions, we did focus our analysis on the 5th school year because it represents the transition year of the first part of Elementary teaching to the second one. For this reason, we separated the grammatical module of the book, identified the grammatical conception that it conveys in comparison to the objectives proposed by the PCNs, verifying if there is any treatment restriction that simplifies the described grammatical content. Teachers answered a questionnaire containing eight questions in order to identify theoretical approaches in which their methodologies are based on, revealing thus how such teachers consider Portuguese language teaching and if they treat the grammatical content as a separate subject or integrate it to textual activities. Finally, we analyzed up to what extent these conceptions, revealed by the book and the teachers who use it, coincide or distinguish themselves.